Efektivitas Pembelajaran Berbasis Proyek dalam Meningkatkan Ekoliterasi: Tinjauan Pustaka Sistematis Berdasarkan PRISMA - Kusumawati Shindi Nur Rahmawati; Siti Mas'ula; Riska Pristiani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effectiveness of Project-Based Learning (PjBL) in enhancing students’ ecoliteracy through a Systematic Literature Review (SLR) based on the PRISMA 2020 framework. The review included peer-reviewed journal articles published between 2020 and 2026, obtained from several international databases such as ScienceDirect, SpringerLink, MDPI, Taylor and Francis, Sage Journals and Google Scholar. A total of 10 articles met the inclusion criteria and were analyzed using thematic synthesis. The findings indicate that PjBL consistently has a positive impact on students’ ecoliteracy across various educational levels. The improvement is reflected in multiple dimensions, including environmental knowledge (cognitive), environmental attitudes and awareness (affective), pro-environmental behavior (conative), and creativity and practical skills. Among these, the cognitive dimension is the most frequently developed, followed by affective and behavioral aspects. Variations in PjBL implementation, such as PjBL-STEM, STEAM, ecopreneurship-based PjBL, and differentiated PjBL, show different strengths in enhancing specific ecoliteracy dimensions. Overall, PjBL is proven to be an effective and holistic learning approach that integrates knowledge, skills, and real-world experiences. However, gaps remain in terms of limited global research distribution and the lack of long-term studies. Therefore, future research is recommended to conduct longitudinal and cross-cultural studies to strengthen the generalizability of findings.